2016
DOI: 10.1155/2016/8348172
|View full text |Cite
|
Sign up to set email alerts
|

Herpes Simplex Virus Hepatitis in an Immunocompetent Host Resembling Hepatic Pyogenic Abscesses

Abstract: Herpes simplex virus (HSV) hepatitis represents a rare complication of HSV infection, which can progress to acute liver failure and, in some cases, death. We describe an immunocompetent 67-year-old male who presented with one week of fever and abdominal pain. Computed tomography (CT) scan and magnetic resonance imaging (MRI) of the abdomen showed multiple bilobar hepatic lesions, some with rim enhancement, compatible with liver abscesses. Subsequent liver biopsy, however, revealed hepatocellular necrosis, HSV-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 16 publications
(23 reference statements)
0
11
0
Order By: Relevance
“…A liver biopsy would show hepatic necrosis, HSV, immunoreactivity to HSV, and intranuclear inclusions . If a liver biopsy is not safe for the patient due to coagulopathy, then HSV PCR in real time would be another test to help diagnose herpes hepatitis . The study done by Beersma et al showed improved early diagnosis and management of herpes hepatitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A liver biopsy would show hepatic necrosis, HSV, immunoreactivity to HSV, and intranuclear inclusions . If a liver biopsy is not safe for the patient due to coagulopathy, then HSV PCR in real time would be another test to help diagnose herpes hepatitis . The study done by Beersma et al showed improved early diagnosis and management of herpes hepatitis.…”
Section: Discussionmentioning
confidence: 99%
“…4,7 If a liver biopsy is not safe for the patient due to coagulopathy, then HSV PCR in real time would be another test to help diagnose herpes hepatitis. 3,8,9 The study done by Beersma et al 10 showed improved early diagnosis and management of herpes hepatitis. The study further showed liver kinetics and HSV DNA load in serum can lead to diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…(b) Immunostaining for HSV‐2 highlights the infected cells. Reprinted with permission from Down et al .’s study …”
Section: Hsv Hepatitismentioning
confidence: 97%
“…The utility of serology including immunoglobulin M and G antibodies is limited by false positive and false negative results. An HSV DNA polymerase chain reaction using blood samples is rapid to perform and has a higher sensitivity and specificity than HSV antibodies …”
Section: Hsv Hepatitismentioning
confidence: 99%
“…Herpes simplex virus type 1 (HSV-1) is a highly prevalent mucocutaneous infection worldwide, however herpes simplex virus (HSV) hepatitis is a rare complication with high morbidity and mortality, accounting for 0.8% of all acute liver failure cases [1,2]. Many cases of HSV hepatitis have been previously reported in the literature in pregnant women and individuals who are immunosuppressed for treatment of various medical conditions such as malignancies.…”
Section: Introductionmentioning
confidence: 99%